2019
DOI: 10.21037/gs.2019.06.09
|View full text |Cite
|
Sign up to set email alerts
|

Inframammary fold subcutaneous cushion assessment using MRI (magnetic resonance imaging)

Abstract: Background: The inframammary fold (IMF) is one of the most important elements in the determination of the aesthetic of the female breast. During mastectomies, it is important to preserve the subcutaneous portion nearby the IMF, attempting that, this preservation will greatly facilitate reconstruction allowing more satisfying aesthetic results. The aim of the present study is to evaluate the thickness of the subcutaneous IMF cushion using magnetic resonance imaging (MRI) acquisition images.Methods: We have gaug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(19 reference statements)
0
2
1
Order By: Relevance
“…In addition, we found that the IMF thickness was positively correlated with breast projection and breast volume. However, a study of Brazilian women measured a larger IMF thickness of 2.40 cm than our data ( 10 ). This may be due to ethnic differences, as previous research has shown that Brazilian women have larger breast sizes than Asian women ( 22 ).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…In addition, we found that the IMF thickness was positively correlated with breast projection and breast volume. However, a study of Brazilian women measured a larger IMF thickness of 2.40 cm than our data ( 10 ). This may be due to ethnic differences, as previous research has shown that Brazilian women have larger breast sizes than Asian women ( 22 ).…”
Section: Discussioncontrasting
confidence: 92%
“…The thickness of IMF reflects the amount of tissue, which is of clinical significance for mammaplasty. The knowledge of IMF thickness can guide glandular resection to preserve a desirable amount of subcutaneous tissue for skin-sparing mastectomy ( 10 ). Besides, the tissue coverage on the prosthesis for breast augmentation can be assessed by reference to the IMF thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation